‘It’s not just immoral!’: The role of moral disengagement and incivility in dehumanising the transgressor of immoral behaviour - Sofía Moreno-Gata; Ramón Rodríguez-Torres; Armando Rodríguez-Pérez; Verónica Betancor (PLoS ONE, 2025)
People who engage in immoral behaviour are often dehumanised. However, they also tend to justify their actions to convince themselves or others that their misconduct is morally acceptable. In this paper, we examine whether moral disengagement mechanisms influence the extent to which a transgressor is perceived as fully human. Further, we assess whether this perception varies based on specific characteristics of the immoral behaviour, such as incivility. To answer these research questions, we conducted two studies with online participants from Spain. In Study 1, participants (N = 302) evaluated a set of 63 behaviours. For every behaviour, they assessed the extent to which it violated each moral foundation from moral foundations theory, its level of incivility, and its potential to elicit dehumanisation. A correlation analysis showed that only the care and purity foundations, along with incivility, were associated with dehumanisation. These results allowed us to select behaviours that varied in incivility for Study 2. In Study 2 (N = 402), we tested the effectiveness of moral disengagement mechanisms employed by the transgressor depending on the level of incivility of the immoral behaviour. To this end, we employed a 3 (moral disengagement mechanisms: moral justification vs. displacement of responsibility vs. distortion of consequences) x 2 (incivility: high vs. low) between-subjects experimental design. The variance analyses showed that using moral justification or displacement of responsibility led to the least amount of dehumanisation, while distortion of consequences resulted in the highest level of dehumanisation. Additionally, immoral behaviours that were high in incivility led to greater dehumanisation than those that were low in incivility, regardless of the moral disengagement mechanism. Overall, our research highlights the significance of different moral disengagement mechanisms and civility as key factors that affect how bystanders perceive the humanness of moral transgressors.